Symptoms and treatment of whooping cough, 1980–82 - English, J.M. (British Homeopathic Journal, 1987)
Questionnaires were obtained from the parents of 71 children who contracted pertussin in 1980–82. They sought to confirm the typical clinical history of the disease, its severity, duration, method of treatment, and any effect this had on its course. They suggest that the disease is milder than it used to be and that whilst antibiotics, including erythromycin, make no significant difference to its course, homœopathic treatment reduces its duration and severity.